1994
DOI: 10.3168/jds.s0022-0302(94)76955-1
|View full text |Cite
|
Sign up to set email alerts
|

Multitrait Restricted Maximum Likelihood Estimates of Genetic and Phenotypic Parameters of Lifetime Performance Traits for Canadian Holsteins

Abstract: Data on 82,835 Holstein cows, daughters of 703 sires and with first calving from September 1979 to December 1984 from 2384 herds enrolled in the Quebec Dairy Herd Analysis Service, were used to estimate genetic and phenotypic parameters of partial and total lifetime performance traits with REML. The model included herd-year-season of first calving, age at first calving, and proven sires as fixed effects and young sires and residuals as random effects. Individual lactation records were precorrected for year-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 28 publications
7
44
2
Order By: Relevance
“…Lower values of heritability for the observed trait were determined by L urdes Kern et al (2014) in the population of Holstein-Friesian cows in Brazil. Established value of heritability for the number of lactations was higher than the value found in the study by Vollema and Groen (1996), while Jairath et al (1994) established a close heritability value of the observed trait.…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…Lower values of heritability for the observed trait were determined by L urdes Kern et al (2014) in the population of Holstein-Friesian cows in Brazil. Established value of heritability for the number of lactations was higher than the value found in the study by Vollema and Groen (1996), while Jairath et al (1994) established a close heritability value of the observed trait.…”
Section: Resultscontrasting
confidence: 44%
“…A certain number of cows was culled immediately upon calving and a start of lactation and in all the animals culled in the first 30 days of lactation the date of the last drying off was taken as a date of culling. Survival rate for subsequent lactations was calculated as a relation of the number of animals which realised given lactation and the number of animals which realised the first lactation (16,572). A total number of realised lactations was 50,382, where each cow included in the analysis realised between 1 and 8 lactations.…”
Section: Methodsmentioning
confidence: 99%
“…'interval from first calving to disposal Nieuwhof et al (1989) reported that the mean productive herd life was 3.4 calvings for US Holsteins as well as for registered Holsteins. For Canadian Holsteins, means of 28 (Jairath et al, 1994) and 43 mo (Hoque and Hodges, 1980) have been reported for productive life and 2.6 (Jairath et al, 1994) and 3.3 calvings. The large differences among means from previous studies and those for Fj cows from the Polish trial clearly demonstrate that these measures of herd life are greatly influenced by feeding and management systems as well as by culling practices.…”
Section: Resultsmentioning
confidence: 99%
“…Heritability estimates for longevity traits (number of calvings, ages at last calving and disposal, DPL, and lifetime DIM) were low, ranging from 0.03 to 0.05 (Table 5). Several researchers (Hoque and Hodges, 1980;Jairath et al, 1994) have reported low to moderate heritabilities for longevity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation